Corporate strategy - Collis, David J. (McGraw-Hill/Irwin, 2005)
This book is an outgrowth of a corporate strategy course we developed and have taught at the Harvard Business School for a number of years. The course has attracted a wide range of students, including those who intend to be consultans, investment bankers, or stock analysts, as well as those who will run family business, or look to long-term careers as general managers....